Participation in Budgeting, Public Accountability, and Performance: Does Internal Oversight Matter? - Edy Fitriawan Syahadat; Sufyan Amirullah; Muhammad Ihsan Ansari (Postgraduate Program Merdeka University, 2024)
This research seeks to examine the effect of participation in budgeting, public accountability on the managerial performance by taking into consideration the moderating effect of internal oversight. We employed 84 respondents of go-vernmental officer in Majene of West Sulawesi. Research variables composed of participation in budgeting, public accountability, and managerial perfor-mance. The hypothesis testing used moderated regression analysis with inter-nal supervision serving as a moderating variable. The results of this research found that participation in budgeting and public accountability are positively associated with managerial performance. These indicate that the level of increase of managerial performance in local government has been determined by participation in budgeting and public accountability. Meanwhile, internal oversight has been found to moderate the effect of participation in budgeting and accountability on managerial performance. It reveals that internal over-sight in governmental sector can strengthen the participation budgeting and public accountability in leading into the increase of managerial performance.DOI: https://doi.org/10.26905/afr.v7i2.12460